INNOVATIVE METHODOLOGICAL TOOL FOR THE ASSESSMENT OF THE PERFORMANCE OF EDUCATIONAL INSTITUTIONS - S. Rakhmanova, М.; V. Kryukov, V. (Revista Gênero e Interdisciplinaridade, 2020)
The article describes a theoretical and methodological approach to assessing the performance of educational facilities of general education on the basis of a balanced scorecard, which is a multifaceted approach to assessing performance, which encapsulates the elements of criteria-based and multi-factor approaches to assessing the performance of educational institutions. The paper also presents the methodological tools for assessing the performance of educational institutions, which is an expanded system of balanced scorecard for assessing the performance of educational institutions, most fully reflecting the dynamics and current state of the performance of educational institutions in the four existing perspectives of the educational institution “finance”, “customers”, “internal processes”, “potential and development” and extended by the fifth perspective “society”. The overall performance of the educational institution makes it possible to evaluate the effectiveness of the activities taking into account the significance of the indicators of each perspective. A procedure for the formation of an information base and documentation support for assessing the performance of educational institutions which provides us with an opportunity to evaluate key indicators for assessing the performance of educational institutions has been developed.